선체구조용 A급 강재의 하이브리드 용접에 대한 열 및 역학적 특성에 관한 연구 - 오종인(CHONG-IN OH); 김영표(YOUNG-PYO KIM); 박호경(HO-KYUNG PARK); 방한서(HAN-SUR BANG) (Han-guk haeyang gonghak hoeji (Online), 2007)
Recently, there has been considerable research in the field of application of Laser-Arc hybrid welding for superstructures, such as ship-structures, transport vehicles etc. However, the study on heat distribution and welding residual stress of hybrid weld by numerical simulation leaves much to be desired. Therefore, in this study, an optimized welding condition and numerical simulation for hybrid welding, using previous numerical analysis to calculate the heat source for hybrid welding, has been analyzed. For this purpose, fundamental welding phenomena of the hybrid process, using Laser and, is investigated. In order to calculate temperature and residual stress distribution in hybrid welds, a finite element heat source model is developed on the basis of experimental results and characteristics of temperature. Residual stress distribution in hybrid welds are understood from the result of simulation, and compared with the experimental values.